Culture and Souvenir Shopping. How do Chinese cultural values play a role in outbound Chinese tourists' souvenir shopping? - Han, Peiyi (UiT The Arctic University of Norway, 2018)
Nowadays, with the rapid economic growth in China, Chinese cultural values are changing. More and more, modern cultural values and Western values can be identified alongside Chinese traditional cultural values based on Confucianism. This applies not only to Chinese people’s way of living, but it is also strongly associated with souvenir shopping when Chinese people travel abroad. The major aim of the study that informs my thesis was to explore and understand how Chinese cultural values play a role in Chinese tourists’ souvenir shopping. A qualitative method was employed to explore Chinese tourists’ attitudes and opinions. After finishing trips to North Cape in Northern Norway, semi-structured interviews were conducted with eight Chinese tourists who were residents of Mainland China, Hong Kong and Taiwan. This qualitative approach allowed the participants to speak relatively freely using their own words, which provided detail and gave rich descriptions in order to explore the phenomenon of souvenir shopping in depth. My study demonstrated how traditional Chinese cultural values still have a dominant status in people’s social life in China. Yet these values can exist alongside modern and Western cultural values, which have gradually been absorbed into Chinese people’s culture. Specifically, the analysis and findings show that by presenting souvenirs as gifts to establish and maintain relationships, Chinese people still cherish family values in traditional ways. Moreover, Chinese people are still trying to enhance and improve their social class by purchasing souvenirs, but they value the actual functions of the souvenirs rather than pay for the brand image. Chinese tourists’ souvenir purchases do not necessarily decrease with their travel experiences since they always purchase gifts for others and some are collectors. Practical issues regarding souvenir shopping are provided. My study also suggests that it is important to reconsider the concept of the term, souvenir, as well as the definition of local products.